2011
DOI: 10.1007/s11033-011-1411-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between GSTM1, GSTT1, and GSTP1 polymorphisms and lung cancer risk in a Turkish population

Abstract: Several studies focused on investigating genetic polymorphisms in order to estimate genetic contribution to lung cancer often showed conflicting results. In this study, we investigated the role of GSTM1, GSTT1, GSTP1 exon 5 and exon 6 polymorphisms on developing lung cancer and histological subtypes in 213 lung cancer patients and 231 controls. GSTM1 null, GSTT1 null, and GSTP1 exon 5 variant genotypes did not show a significant risk for developing lung cancer overall. Significant association was noted between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
3
18
0
3
Order By: Relevance
“…Their results revealed that no significant association was found for any of the analyzed polymorphisms and overall lung cancer risk, although their subgroup analysis revealed smoking-specific effects [48] . The latest study of a Turkish population showed that the GSTP1 exon 6 polymorphism (rs4891) may be an important factor in determining lung cancer susceptibility [49] . There is no risk genotype or allele for rs7208693, so it is difficult to evaluate the combination of GSTP1 and MPO with risk.…”
Section: Discussionmentioning
confidence: 99%
“…Their results revealed that no significant association was found for any of the analyzed polymorphisms and overall lung cancer risk, although their subgroup analysis revealed smoking-specific effects [48] . The latest study of a Turkish population showed that the GSTP1 exon 6 polymorphism (rs4891) may be an important factor in determining lung cancer susceptibility [49] . There is no risk genotype or allele for rs7208693, so it is difficult to evaluate the combination of GSTP1 and MPO with risk.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows no significant difference between TP53 and CYP2E1 gene interactions and the risk of NSCLC (top results). We then looked further to find if these variant genotypes would be associated with increased NSCLC risk if combined with the GSTM1, GSTT1, and GSTP1 polymorphisms from our earlier study (19) and found a significant association for TP53 codon72 Arg/Pro and Pro/ Pro in combination with the GSTM1 null genotypes. A similar significant association with NSCLC risk was found for the combinations of TP53 codon72 Arg/Pro and Pro/ Pro with the GSTT1 null and the GSTP1 (Ala114Val) genotypes (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…We have also analysed the interactions between TP53 and CYP2E1 gene polymorphisms and the GST gene (GSTM1, GSTT1 and GSTP1) polymorphisms that we had previously determined in the same patients in our 2012 study (19) to see whether they may affect the NSCLC risk. Our results confirm the findings of Klinchid et al (33), who found a significant association between the TP53 codon72 variant and GSTM1 null combination and NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng-Hui Hu, Yi-Wei Lin, Xin Xu, Hong Chen, Ye-Qing Mao, Jian Wu, Yi Zhu, Xiang-Lai Xu, Li-Ping Xie* McGrath et al, 2006), lung (Ada et al, 2012;Lopez-Cima et al, 2012), breast (Oliveira et al, 2010;de Aguiar et al, 2012), head and neck (Suzen et al, 2007;Nosheen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%